Capsaicin Enhances Glutamatergic Synaptic Transmission to Neonatal Rat Hypoglossal Motor Neurons via a TRPV1-Independent Mechanism - Thakre, Prajwal P.; Bellingham, Mark C. (Frontiers in Cellular Neuroscience, 2017)
We investigated whether capsaicin modulated synaptic transmission to hypoglossal motor neurons (HMNs) by acting on transient receptor potential vanilloid type 1 (TRPV1) receptors. Using whole-cell patch clamp recording from neonatal rat HMNs, we found that capsaicin increased spontaneous excitatory post-synaptic current (sEPSC) frequency and amplitude. Interestingly, the only effect of capsaicin on spontaneous inhibitory post-synaptic currents (sIPSCs) was a significant decrease in sIPSC amplitude without altering frequency, indicating a post-synaptic mechanism of action. The frequency of miniature excitatory post-synaptic currents (mEPSCs), recorded in the presence of tetrodotoxin (TTX), was also increased by capsaicin, but capsaicin did not alter mEPSC amplitude, consistent with a pre-synaptic mechanism of action. A negative shift in membrane current (Iholding) was elicited by capsaicin under both recording conditions. The effect of capsaicin on excitatory synaptic transmission remained unchanged in the presence of the TRPV1 antagonists, capsazepine or SB366791, suggesting that capsaicin acts to modulate EPSCs via a mechanism which does not require TRPV1 activation. Capsaicin, however, did not alter evoked excitatory post-synaptic currents (eEPSCs) or the paired-pulse ratio (PPR) of eEPSCs. Repetitive action potential (AP) firing in HMNs was also unaltered by capsaicin, indicating that capsaicin does not change HMN intrinsic excitability. We have demonstrated that capsaicin modulates glutamatergic excitatory, as well as glycinergic inhibitory, synaptic transmission in HMNs by differing pre- and post-synaptic mechanisms. These results expand our understanding regarding the extent to which capsaicin can modulate synaptic transmission to central neurons.